2020
DOI: 10.1038/s41586-019-1871-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of free-standing monolayer amorphous carbon

Abstract: Bulk amorphous materials have been studied extensively and are used widely. Yet, their atomic arrangement remains an open issue. They are generally believed to be Zachariasen continuous random networks (Z-CRNs) 1 , but recent experimental evidence favours the competing crystallite model in the case of amorphous silicon 2-4 .Corresponding questions in 2D materials are wide open. Here we report the synthesis of centimetre-scale, freestanding, continuous, and stable monolayer amorphous carbon (MAC), topologically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
294
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(323 citation statements)
references
References 36 publications
26
294
0
3
Order By: Relevance
“…60% after 5 min exposure, while leveling off at approximately twice the value of the nitrogen-free material after 10 min. This is consistent with the introduction of both N-sites and defects; these are known to result in (i) an increased density of mid-gap localized/surface states (Van Tuan et al, 2012;Zhong et al, 2014;Velický et al, 2019;Toh et al, 2020) which lead to increased interfacial capacitance (Wiggins-Camacho and Stevenson, 2009;Tian et al, 2015;Velický et al, 2019), albeit at the expense of delocalization; and (ii) an increase in electrode roughness and consequently its electrochemical specific surface area (ECSA). A similar increase of the capacitance by a factor of 2 is observed at 10 Hz; notably, a comparison of values obtained at 0.1 vs. 10 Hz indicates dispersion in the capacitive response.…”
Section: Electrochemical Studies Of Anc:n Electrode Materialssupporting
confidence: 73%
“…60% after 5 min exposure, while leveling off at approximately twice the value of the nitrogen-free material after 10 min. This is consistent with the introduction of both N-sites and defects; these are known to result in (i) an increased density of mid-gap localized/surface states (Van Tuan et al, 2012;Zhong et al, 2014;Velický et al, 2019;Toh et al, 2020) which lead to increased interfacial capacitance (Wiggins-Camacho and Stevenson, 2009;Tian et al, 2015;Velický et al, 2019), albeit at the expense of delocalization; and (ii) an increase in electrode roughness and consequently its electrochemical specific surface area (ECSA). A similar increase of the capacitance by a factor of 2 is observed at 10 Hz; notably, a comparison of values obtained at 0.1 vs. 10 Hz indicates dispersion in the capacitive response.…”
Section: Electrochemical Studies Of Anc:n Electrode Materialssupporting
confidence: 73%
“…Different from previously reported carbon amorphous monolayers 13 (0.6 nm thickness), our amorphous PtSe x layer is made of Pt and Se atoms with more complicated coordination and, to the best of our knowledge, is the rst binary amorphous layer. Notably, our amorphous layer can be thermodynamically stable in a 2D form with a thickness down to 1 nm.…”
Section: Fabrication Of Atomically Thin Amorphous Ptse Xmentioning
confidence: 85%
“…Their arguments are in line with the views of Cheng. In 2020, Özyilmaz group prepared free-standing monolayer amorphous carbon, and it was found that it was reasonable to describe its structure by MRO model rather than CRN model [23].…”
Section: Introductionmentioning
confidence: 99%